Temporal dynamics and composition of ocular surface microbiota in C57BL/6J mice: uncovering a 12h ultradian rhythm - Jiao, Xinwei; Li, Zhijie (Frontiers in Cellular and Infection Microbiology, 2023)
PURPOSE. This study aimed to investigate the presence of rhythmic fluctuations in the composition, abundance, and functions of commensal core bacteria on the ocular surface of C57BL/6J mice. METHODS. Male C57BL/6J mice, aged 12 weeks, were subjected to a 12-hour light/12-hour dark cycle. Ocular surface tissue samples were collected at four time points (ZT) over a 24-hour period at six-hour intervals. The core ocular surface microbiota's oscillation cycles and frequencies were assessed using 16S rRNA gene sequencing targeting the V3-V4 region, along with the JTK_CYCLE algorithm. Functional predictions of these bacteria were conducted using PICRUSt2. RESULTS. Deep sequencing of the ocular surface microbiota highlighted the high abundance of commensal bacteria, with Proteobacteria, Actinobacteriota, and Firmicutes collectively constituting over 90% of the total sample abundance. Among the 22 core bacterial genera, 11 exhibited robust 12-hour rhythms, including Halomonas, Pelagibacterium, Pseudomonas, Nesterenkonia, norank_f_Hyphomonadaceae, Stenotrophomonas, Anoxybacillus, Acinetobacter, Zoogloea, Brevibacillus, and Ralstonia. Further taxonomic analysis indicated significant intra-cluster similarities and inter-cluster differences at the order, family, and genus levels during ZT0/12 and ZT6/18. Community interaction networks and functional prediction analyses revealed synchronized 12-hour rhythmic oscillations in neural, immune, metabolic, and other pathways associated with symbiotic bacteria. CONCLUSIONS. This study demonstrates the presence of ultradian rhythmic oscillations in commensal bacteria on the ocular surface of normal C57BL/6J mice, with a 12-hour cycle. These findings suggest a crucial role for ultradian rhythms in maintaining ocular surface homeostasis in the host.